Measurements of ν_μ and ν_μ + ν_μ charged-current cross-sections without detected pions or protons on water and hydrocarbon at a mean anti-neutrino energy of 0.86 GeV. (2nd March 2021) - Abe, K; Akhlaq, N; Akutsu, R; Ali, A; Alt, C; Andreopoulos, C; Anthony, L; Antonova, M; Aoki, S; Ariga, A; Arihara, T; Asada, Y; et al.
Abstract: We report measurements of the flux-integrated ν_μ and ν_μ+ν_μ charged-current cross-sections on water and hydrocarbon targets using the T2K anti-neutrino beam with a mean beam energy of 0.86 GeV. The signal is defined as the (anti-)neutrino charged-current interaction with one induced μ^± and no detected charged pion or proton. These measurements are performed using a new WAGASCI module recently added to the T2K setup in combination with the INGRID Proton Module. The phase space of muons is restricted to the high-detection efficiency region, p_μ>400 MeV/c and θ_μ<30^°, in the laboratory frame. An absence of pions and protons in the detectable phase spaces of p_π>200 MeV/c, θ_π<70^° and p_p>600 MeV/c, θ_p<70^° is required. In this paper, both the ν_μ cross-sections and ν_μ+ν_μ cross-sections on water and hydrocarbon targets and their ratios are provided by using the D'Agostini unfolding method. The results of the integrated ν_μ cross-section measurements over this phase space are σ_H_2O=(1.082±0.068(stat.)^+0.145_-0.128(syst.)) × 10^-39 cm^2 / nucleon, σ_CH=(1.096±0.054(stat.)^+0.132_-0.117(syst.)) × 10^-39 cm^2 / nucleon, and σ_H_2O/σ_CH = 0.987±0.078(stat.)^+0.093_-0.090(syst.) . The ν_μ+ν_μ cross-section is σ_H_2O = (1.155±0.064(stat.)^+0.148_-0.129(syst.)) × 10^-39 cm^2 / nucleon, σ_CH=(1.159±0.049(stat.)^+0.129_-0.115(syst.)) × 10^-39 cm^2 / nucleon, and σ_H_2O/σ_CH=0.996±0.069(stat.)^+0.083_-0.078(syst.) .